Visual Dramaturgy and the Construction of Digital Dakwah Aesthetics on Instagram: A Study of @ppsunandrajat - Ainur Rofiq; Rifaldi Abrorul Umam; Azkiyah Ramadhani (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
: This study aims to analyze the construction of digital dakwah aesthetics through visual dramaturgy and symbolic communication in the Instagram content of @ppsunandrajat, the official account of Pondok Pesantren Sunan Drajat (PPSD) Lamongan. The study employed a qualitative approach to digital content analysis, integrating Erving Goffman’s dramaturgical perspective and Roland Barthes’ semiotic framework. Data were collected through systematic observation of Instagram content published between 2024 and 2026, visual documentation, and in-depth interviews with three key informants involved in content production and management. The findings reveal that Instagram functions not only as an information-sharing platform but also as a strategic medium for constructing institutional identity and for digital dakwah communication. Visual representations of religious authority figures, mosque architecture, institutional color palettes, and student activities are deliberately organized to create a coherent image of a pesantren that is both religiously authentic and technologically adaptive. Through dramaturgical analysis, the account operates as a digital front stage where impression management is carefully maintained. Meanwhile, semiotic analysis demonstrates that visual elements communicate denotative, connotative, and mythological meanings associated with spiritual authority, educational excellence, and institutional legitimacy. This study contributes theoretically to the development of digital dakwah studies by highlighting the significance of visual communication in shaping religious identity within contemporary social media environments. Practically, the findings provide insights for Islamic educational institutions in developing effective, audience-oriented, and visually persuasive digital dakwah strategies